(untitled) (Research, Society and Development, 2023)
Introduction: Autism Spectrum Disorder (ASD) is a condition that affects neurodevelopment, causing deficits in communication skills, socialization and adaptation to the external environment. Caring for children with ASD requires changes in the lives of the whole family, creating a physical and emotional burden for the caregiver. Mothers are the main caregivers for their children and therefore suffer the most from anxiety disorders, depression and chronic stress. Objective: To assess anxiety and depression in mothers of children with ASD and factors associated with this prevalence. Methods: will include mothers of autistic children who will participate in the survey, by Google Forms of the Patient Health Questionnaire-9 (PHQ-9) and General Anxiety Disorder (GAD-7) questionnaires. Results: The PHQ-9 identified that the standard average among the participants was 13.83 points, where the maximum score was 27 and the minimum 0 points. On the GAD-7, the average sum of points among the participants was 12.63, with the highest score being 21 points and the lowest 2 points. Conclusion: The results show that mothers of children with ASD have a high incidence of depressive and anxiety disorders. In addition to stress, physical and emotional exhaustion, due to the centralization of care in mothers. In addition, financial dependence exposes these women to situations of vulnerability and violence. Finally, we emphasize the need to formulate actions for this target group in order to improve the quality of life of these mothers.